Peramalan Harga Saham dengan Brownian Motion - Maulana, Yasir; Wiharno, Herma (Indonesian Journal of Strategic Management, 2024)
In financial markets modelling, especially stock markets, Brownian Motion plays an important role in building a statistical model. One of the most important concepts in building such financial models is to understand geometric Brownian motion, which is a special case of the Brownian Motion Process. PT. Petrindo Jaya Kreasi, Tbk (CUAN) is a holding company whose business is in the mineral mining and energy sectors. The share prices in this study are based on daily data on the Closing Price of PT shares. Petrindo Jaya Kreasi, Tbk for the period 15 January 2024 to 29 February 2024. The Brown Motion parameter estimation model with P0 = 13,425 obtained µ = -0.021116964, the value of σ = 0.07803483 and σ² = 0.006089435. Based on the model formed, it is necessary to calculate the level of accuracy using the Mean Absolute Percentage Error (MAPE). From the calculation results, the MAPE value is found to be in the range of 21%-50%, namely 22.3%. So it can be concluded that the resulting average error deviation shows the usual level of forecasting accuracy.